1993
DOI: 10.1111/j.1365-2222.1993.tb00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of allergen avoidance at high altitude on serum markers of eosinophil activation in children with allergic asthma

Abstract: A cohort of 12 asthmatic children was followed over several months, during which they moved back and forth from an allergen-free to an allergen-rich environment at high and low altitude, respectively. The children were treated with non-steroidal anti-asthmatic drugs as clinically needed. Histamine PC20-FEV1 was unaltered during the study period, whereas serum levels of eosinophil cationic protein (ECP) and eosinophil protein X (EPX) showed significant changes when the children were exposed to the offending all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 23 publications
(16 reference statements)
5
48
0
1
Order By: Relevance
“…It has been shown that children with dust mite allergy who have symptoms at sea level where dust mite exposure is high may clinically improve by moving to higher altitudes where dust mites are not as prominent [16]. Thus, when it is practical, avoiding allergen exposure for sensitive individuals is a useful tool in the management of the patient.…”
Section: O P Y R Ig H T G E N E R a L P R A C T Ic E A Ir W A Y S Gmentioning
confidence: 99%
“…It has been shown that children with dust mite allergy who have symptoms at sea level where dust mite exposure is high may clinically improve by moving to higher altitudes where dust mites are not as prominent [16]. Thus, when it is practical, avoiding allergen exposure for sensitive individuals is a useful tool in the management of the patient.…”
Section: O P Y R Ig H T G E N E R a L P R A C T Ic E A Ir W A Y S Gmentioning
confidence: 99%
“…Besides standard treatment with inhaled and systemic glucocorticoids (GC) and b 2 -agonists, which aim on the reduction of local and systemic inflammation and bronchodilatation, high-altitude climate therapy is one major further treatment option for asthmatic patients [10][11][12][13][14]. Main factors that are suggested to influence asthma in high-altitude climate therapy are allergen avoidance, increased cortisol and catecholamine level, the dry air and high UV light exposure [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…25 Other similar studies assessed changes of environment in which patients were moved to high altitude places where mite levels were low; in these cases, sensitized patients also improved. [26][27][28] A recent prospective study analyzed environment care measures for children at risk since birth, and demonstrated that there was no difference in sensitization to air allergens between the cared group and controls (in which no environmental measures were undertaken); there was, however, a difference in lung function between groups at age 3 years. 38 Studies that aimed to decrease allergen exposure in households reached conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Various published papers had shown that there are variable responses to allergen control measures; the study design and the response assessments, however, varied among these papers, which has generated controversies among physicians. [17][18][19][20][21][22][23][24][25][26][27][28] The purpose of this paper was to discuss the difficulty of controlling allergen exposure and to review various studies in different environments within which individuals spend their days.…”
Section: Introductionmentioning
confidence: 99%